2012
DOI: 10.3109/00365521.2012.660542
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate markers and clinical indices, alone or combined, as indicators for endoscopic remission in anti-TNF-treated luminal Crohn's disease

Abstract: Clinical scores commonly used in the assessment of disease activity are unreliable at differentiating endoscopic remission from active CD. Despite this, a score based on a combination of fecal calprotectin and the HBI is a new promising tool for identifying endoscopic remission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
85
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(93 citation statements)
references
References 33 publications
5
85
1
2
Order By: Relevance
“…Fecal calprotectin (fC) is a marker of mucosal CD activity, correlates with excretion of 111 indium-labelled granulocytes in stool, CRP, faecal lactoferrin 32-36 and predicts active disease at endoscopy [37][38][39] . Despite several limitations it seems a reasonable marker of global inflammatory burden as an endpoint 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Fecal calprotectin (fC) is a marker of mucosal CD activity, correlates with excretion of 111 indium-labelled granulocytes in stool, CRP, faecal lactoferrin 32-36 and predicts active disease at endoscopy [37][38][39] . Despite several limitations it seems a reasonable marker of global inflammatory burden as an endpoint 40 .…”
Section: Discussionmentioning
confidence: 99%
“…(28 ranges from a minimum of 0 to a maximum of 30. Somatization severity was categorized, using the total PHQ-15 score, into high (total PHQ-15 ≥15), medium (10)(11)(12)(13)(14), low (5-9) and minimal (≤4) levels of somatization severity,…”
Section: Definition Of Anxiety or Depressionmentioning
confidence: 99%
“…(6-8) Furthermore, recent observational data from longitudinal studies suggest that mood disorders, including anxiety and depression, may be associated with adverse disease outcomes and reduced quality of life. (9) However, many studies designed to investigate these issues have used clinical disease activity indices to assess disease activity, rather than gold-standard investigations such as ileocolonoscopy or small bowel imaging, or fecal biomarkers of intestinal inflammation and, given that the correlation between these tools and objective measures of inflammation may be variable, (10)(11)(12)(13)(14) the implication of these results is uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies observed considerable heterogeneity between the various tests due to a lack of diagnostic methodology standardization as there are so few studies evaluating endoscopic activity. The two studies proposed different cut-offs for FC: 50 µg/g (5,21), 100 µg/g (17,22,23), 250 µg/g (24,25) and 274 µg/g (26), with no agreement on the optimum cut-off level.…”
Section: Introductionmentioning
confidence: 99%